Structured software development with the IPIDDDT method - A lean method for small agile organizations - Ahvonen, Jori (fi=Turun yliopisto|en=University of Turku|, 2010)
A software development process is a predetermined sequence of steps to create a piece of software. A software development process is used, so that an implementing organization could gain significant benefits. The benefits for software development companies, that can be attributed to software process improvement efforts, are improved predictability in the development effort and improved quality software products. The implementation, maintenance, and management of a software process as well as the software process improvement efforts are expensive. Especially the implementation phase is expensive with a best case scenario of a slow return on investment. Software processes are rare in very small software development companies because of the cost of implementation and an improbable return on investment. This study presents a new method to enable benefits that are usually related to software process improvement to small companies with a low cost. The study presents reasons for the development of the method, a description of the method, and an implementation process for the method, as well as a theoretical case study of a method implementation. The study's focus is on describing the method. The theoretical use case is used to illustrate the theory of the method and the implementation process of the method. The study ends with a few conclusions on the method and on the method's implementation process. The main conclusion is that the method requires further study as well as implementation experiments to asses the value of the method.